A short guide to a long life [compact disc, unabridged] - Agus, David, 1965- (Simon And Schuster, 2014)
Divided into three sections (What to Do, What to Avoid, and Doctor's Orders) that provide the definitive answers to many common and not-so-common questions: Who should take a baby aspirin daily? Are flu shots safe? What constitutes 'healthy' foods? Why is it important to protect your senses? Are airport scanners hazardous? Dr. Agus will help you develop new patterns of personal health care using inexpensive and widely accessible tools that are based on the latest and most reliable science.